2018
DOI: 10.1002/jcp.26443
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 silencing improves oxaliplatin efficacy through acetylation of MnSOD in colon cancer

Abstract: Sirtuin 3 (SIRT3) is the major mitochondria deacetylase and regulates ROS levels by targeting several key proteins, such as those involved in mitochondrial function and antioxidant defenses. This way, SIRT3 balances ROS production and scavenging and promotes cell survival. The aim of this study was to analyze the effect of SIRT3 silencing on the antioxidant response in SW620 colon cancer cell line, and whether this intervention could improve efficacy of oxaliplatin, a common drug used to treat colon cancer. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Previous studies demonstrated that mitochondrial ROS generation is modulated by SIRT3 in a variety of cells [ 26 29 ]. Thus, the mitochondrial redox status was compared between SIRT3 WT and SIRT3 KO BMDMs using MitoSOX Red, a highly selective fluorescent probe for the detection of mitochondrial O 2 − [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that mitochondrial ROS generation is modulated by SIRT3 in a variety of cells [ 26 29 ]. Thus, the mitochondrial redox status was compared between SIRT3 WT and SIRT3 KO BMDMs using MitoSOX Red, a highly selective fluorescent probe for the detection of mitochondrial O 2 − [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data represent three independent experiments (c left), and values represent means (± SEM) from three or four independent experiments performed in triplicate (a and b). Previous studies demonstrated that mitochondrial ROS generation is modulated by SIRT3 in a variety of cells [26][27][28][29]. Thus, the mitochondrial redox status was compared between SIRT3 WT and SIRT3 KO BMDMs using MitoSOX Red, a highly selective fluorescent probe for the detection of mitochondrial O 2 − [30].…”
Section: Sirt3 Deficiency Leads To Increased Inflammatory Responses Amentioning
confidence: 99%
“…SIRT3 plays a conflicting role not only in different types of cancer, such as gastric cancer [133,134], lung cancer [49,135,136], and colon cancer [137][138][139][140], but also in malignancies originating from the same types of tissue. SIRT3 has been found to affect tumorigenesis by depleting reactive oxygen species (ROS), modulating metabolism, and regulating proliferative or apoptotic pathways [141].…”
Section: Sirtuins In Tumorigenesismentioning
confidence: 99%
“…Sirtuin 3 (Sirt3), a type of NAD-dependent deacetylase expressed mainly in mitochondria, has recently been reported to have multiple effects on mitochondrial protection in response to several types of stress, such as oxidative stress (Torrens-Mas et al 2018), hyperglycemia (Nassir et al 2018), fatty acid composition (Chabi et al 2018), and myocardial infarction (Hou et al 2015). At the molecular level, Sirt3 protects against p53-mediated mitochondrial damage and neuronal death in a deacetylase activity-dependent manner (Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%